Anaerobic fermentation effectively reduces concentration of total tannins in Chromolaena odorata - Yelly M. Mullik; Muhammad Ridla; Iwan Prihantoro; Marthen L. Mullik (Indonesian Center for Animal Research and Development (ICARD), 2016)
Chromolaena odorata is a potential feed source but its usage is hampered by presence of various secondary metabolic compounds in plant’s tissues. One group of them is tannin. This experiment was aimed to evaluate various pre-treatment methods on total tannin concentration and in vitro digestibility of dry- and organic-matter. An 8 x 3 completely randomized experimental design was employed to test 8 different treatments. The treatments were: Fresh = freshly-chopped chromolaena leaves as control, Sun-dried = sun-dried (3x 24 hours) chromolaena leaves, Oven-dried = oven-dried (60oC for 24 hours) chromolaena leaves, Boiled = water-boiled (5 minutes) chromolaena leaves, RenWater = water-soaked (4 hours) chromolaena leaves, RenNaOH = NaOH-soaked (4 hours) chromolaena leaves, RenHCl = HCl-soaked (4 hours) chromolaena leaves, and Fermented = anaerobically-fermented (21 days) chromolaena leaves. Parameters measured were concentration of total tannins and nutrient content. The results showed that application of low heat (Sun-dried), hot water (Boiled), water soaking (RenWater), or unaeobic fermentation technique significantly reduced total tannin by 43% into 62% compared to control. The highest suppression (62%) was achieved by Fermented treatment. In the contrary, medium heat application (oven-dried at 60°C) or chemicaltreatments (HCl or NaOH) had no effect. Protein content of chromolaena was improved by 60% and crude fiber was reduced by 32% in Fermentaed treatment compared to the control. It could be concluded that anaerobic fermentation can be used an effective strategy to reduce tannin concentration in Chromolaena odorata without affecting its feeding value.